The role of diagnostic ultrasound imaging for patients with known prostate cancer within an active surveillance pathway: A systematic review. (February 2022) - Parker, Pamela; Twiddy, Maureen; Whybrow, Paul; Rigby, Alan; Simms, Matthew
Background: The use of multiparametric magnetic resonance imaging (mpMRI) within active surveillance of prostate cancer programmes is identified by the UK National Institute for Health and Care Excellence (NICE guideline NG 131 2019) as having a role for monitoring disease. The widespread demands on mpMRI capacity may limit its use in surveillance. It is therefore timely to review the options that modern ultrasound imaging present to this cohort of patients in the monitoring of prostate cancer. Methods: Between April and September 2020, 10 databases were searched to recruit studies for the review. Three reviewers evaluated the publications for inclusion. Characteristics including the inclusion criteria for the study cohort, how disease was determined, identification of disease progression, and the modality and mode of imaging used were reviewed. Given the paucity of full text articles, a meta-analysis was not possible. A narrative review was undertaken. Results: In total, 12 studies, utilising the range of ultrasound parameters of B-mode, micro-ultrasound, colour Doppler, contrast ultrasound and elastography were included. The review demonstrated that micro-ultrasound offers promise as an imaging tool comparable with mpMRI. However, this is an emerging technology with limited availability. Analysis of the data further demonstrated that by combining the diagnostic features provided by multiple modes reviewed, ultrasound has a role in the diagnostic imaging of patients on active surveillance. Conclusion: Providing a multiparametric approach is utilised, stable ultrasound findings may allow for increased intervals between biopsy for men on surveillance. The advent of micro-US offers promise as an imaging modality within an active surveillance pathway but requires further verification.